Purification and Characterization of Streptomyces sp. IK Chitinase - Sebastian Margino; Agustinus Joko Nugroho; Widya Asmara (Universitas Gadjah Mada, 2010)
Streptomyces sp. IK isolated from compost inoculants, could produce extra cellular chitinase in a medium containing 0.2% (w/v) colloidal chitin, fermented for 96 hours at 30oC. The enzyme was purified by a combination of ammonium sulphate precipitation and DEAE-Cellulose anion-exchange chromatography. On SDS-polyacrylamide gel electrophoresis analysis, the purified enzyme showed a mass of 71 kDa. Chitinase was optimally active at pH of 6.7 and at 37oC. Km value and Vmax of the protein for colloidal chitin were 2.92 mg/ml and 4.26 ìg/h, respectively.Key words : chitinase, Streptomyces, purification, characterization